Repair of iatrogenic furcal perforation with mineral trioxide aggregate: A seven-year follow-up - Camilo do Carmo Monteiro, Jardel [UNESP]; Rodrigues Tonetto, Mateus; Coêlho Bandeca, Matheus; Henrique Borges, Alvaro; Cláudio Martins Segalla, José [UNESP]; Cristina Fagundes Jordão-Basso, Keren [UNESP]; Fernando Sanchez-Puetate, Cristian [UNESP]; Carlos Kuga, Milton [UNESP] (My University, 2017)
Teeth with furcal perforation present difficult resolution and dubious prognosis. Several materials have been proposed and calcium silicate-based cements such as mineral trioxide aggregate (MTA) are the most recommended. However, its longterm clinical behavior still remains poorly understood. The present study reports a clinical case of furcal perforation repair using Angelus MTA, with a 7-year follow-up. Patient sought treatment 2 months after iatrogenic accident. First lower right molar presented clinical signs such as fistula and bone loss between mesial and distal roots. Firstly, all root canals were treated and then furcal perforation was sealed with MTA Angelus and the dental crown was restored with composite resin. Radiographic evaluation was immediately performed to analyze the furcal perforation filling. After 7 years, a new clinical and imaging evaluation using periapical radiography and cone-beam computed tomography (CBCT) showed absence of clinical signs and symptoms, and alveolar bone reconstitution with periodontal space reduction. Angelus MTA presented good clinical behavior in the iatrogenic furcal perforation resolution based on long-term clinical evidence.
Keywords: Endodontics; Furcation Perforation; Mineral Trioxide Aggregate; Root Canal Treatment; Root Perforation; Tooth Perforations